Addition of vasopressin synthetic analogue [V4Q5]dDAVP to standard chemotherapy enhances tumour growth inhibition and impairs metastatic spread in aggressive breast tumour models - Garona, Juan (2016)
[V4Q5]dDAVP is a novel 2nd generation vasopressin analogue with robust antitumour activity against metastatic breast cancer. We recently reported that, by acting on vasopressin V2r membrane receptor present in tumour cells and microvascular endothelium, [V4Q5]dDAVP inhibits angiogenesis and metastatic progression of the disease without overt toxicity. Despite chemotherapy remaining as a primary therapeutic option for aggressive breast cancer, its use is limited by low selectivity and associated adverse effects. In this regard, we evaluated potential combinational benefits by adding [V4Q5]dDAVP to standard-of-care chemotherapy. In vitro, combination of [V4Q5]dDAVP with sub-IC50 concentrations of paclitaxel or carmustine resulted in a cooperative inhibition of breast cancer cell growth in comparison to single-agent therapy. In vivo antitumour efficacy of [V4Q5]dDAVP addition to chemotherapy was first evaluated using the triple-negative MDA-MB-231 breast cancer xenograft model. Tumour-bearing mice were treated with i.v. injections of [V4Q5]dDAVP (0.3 lg/kg, thrice weekly) in combination with weekly cycles of paclitaxel (10 mg/kg i.p.). After 6 weeks of treatment, combination regimen resulted in greater tumour growth inhibition compared to monotherapy. [V4Q5]dDAVP addition was also associated with reduction of local aggressiveness, and impairment of tumour invasion and infiltration of the skin. Benefits of combined therapy were confirmed in the hormone-independent and metastatic F3II breast cancer model by combining [V4Q5]dDAVP with carmustine (25 mg/kg i.p.). Interestingly, [V4Q5]dDAVP plus cytotoxic agents severely impaired colony forming ability of tumour cells and inhibited breast cancer metastasis to lung. The present study shows that [V4Q5]dDAVPmay complement conventional chemotherapy by modulating metastatic progression and early stages of microtumour establishment, and thus supports further preclinical testing of the compound for the management of aggressive breast cancer.